2016
DOI: 10.1159/000447516
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synthetic Cannabinoids on P-Wave Dispersion: An Observational Study

Abstract: Objective: The aim of this study was to investigate the effect of synthetic cannabinoids (SC) on P-wave dispersion (PD) in patients who consume SC. Materials and Methods: The study population included 72 patients who consumed SC and 36 age- and sex-matched healthy controls. The severity of addiction was detected using the addiction profile index (BAPI). The PD was measured by 12-lead ECG obtained upon admission to hospital. Statistical analyses were performed using the SPSS v20.0 statistical software package. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…In a recent study published by Aydin Sunbul et al, a significant association between higher PWD and chronic SCB consumption was demonstrated. In their well-defined study, PWD was significantly higher in the patient group consuming SCBs compared to healthy controls and positively correlated with the severity of addiction (Aydin Sunbul et al, 2016). Similarly, increased PWD was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study published by Aydin Sunbul et al, a significant association between higher PWD and chronic SCB consumption was demonstrated. In their well-defined study, PWD was significantly higher in the patient group consuming SCBs compared to healthy controls and positively correlated with the severity of addiction (Aydin Sunbul et al, 2016). Similarly, increased PWD was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing interest to the cardiovascular effects of SCBs due to the fact that many young patients consuming SCBs involve the emergency services because of the side effects of the substance (Aydin Sunbul et al, 2016). However, the exact mechanism underlying the cardiovascular side effects of SCBs is not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations